2016
DOI: 10.1177/0022002714560345
|View full text |Cite
|
Sign up to set email alerts
|

Buying Influence? Assessing the Political Effects of China’s International Trade

Abstract: It is widely believed that China’s growing links to the global economy are translating into increased Chinese political influence abroad. This article explores this possibility quantitatively by examining whether increased trade with China correlates with an increased willingness by countries to accommodate Chinese interests. I use newly collected data that capture cross-national variation in the willingness of individual countries to support Chinese government positions relating to Taiwan and Tibet, and China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 26 publications
2
22
1
1
Order By: Relevance
“…In the first case, despite the generally accepted mercantilist argument (Heaton, 1937; Landreth & Colander, 2002), we found that the share of imports from China plays a greater role than exports to China in terms of foreign policy accommodation. This result is consistent with other recent findings (Kastner, 2014; Strüver, 2016), which reflects that the mercantilist view of trade is fundamentally outdated in the framework of a globalized economy. Exports have by now become inseparable from imports, since the majority of exports from one country to another often involve a complex cooperation of domestic and foreign suppliers via value chains.…”
Section: Resultssupporting
confidence: 93%
“…In the first case, despite the generally accepted mercantilist argument (Heaton, 1937; Landreth & Colander, 2002), we found that the share of imports from China plays a greater role than exports to China in terms of foreign policy accommodation. This result is consistent with other recent findings (Kastner, 2014; Strüver, 2016), which reflects that the mercantilist view of trade is fundamentally outdated in the framework of a globalized economy. Exports have by now become inseparable from imports, since the majority of exports from one country to another often involve a complex cooperation of domestic and foreign suppliers via value chains.…”
Section: Resultssupporting
confidence: 93%
“…Geo-economic competition and the weaponization of interdependence are already attracting growing interest from the academic and policy scholars (Blackwill and Harris, 2016;Farrell and Newman, 2019;Wright, 2017). It is difficult to ignore the similarities between Germany's economic penetration of the Ottoman Empire through sovereign debt, arms deals, and infrastructure projects such as the Berlin-Baghdad Railroad; its cooptation of Ottoman civilian and military elites; and its subsequent control over Ottoman policy and the current policies and actions of China (Dreher et al, 2018(Dreher et al, , 2019Flores-Macias and Kreps, 2013;Kastner, 2016;Norris, 2016;Strüver, 2016;Tuman and Shirali, 2017), as well as Russia (e.g. Sherr, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The PENS literature, though, has long called into question the thesis that there is a one-to-one correspondence between economic stimuli and political behavior [12,17,75]. After all, economic relations often entail both positive and negative economic stimuli.…”
Section: The Translation Issuementioning
confidence: 99%